SME financial distress and the macroeconomic recovery: A microsimulation approach - Janez Kren; Martina Lawless; Gerard McGuinness; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2022)
This paper models the immediate impact of the COVID-19 pandemic on Irish SMEs and extrapolates forward their performance as restrictions ease. Our baseline scenario shows a steady recovery path for the median firm. However, indicators of financial difficulties remain persistently high with the share of highly distressed firms reaching twenty-one per cent in 2024 in scenarios without firm exit. With exit of the most financially distressed firms, the patterns of financial characteristics return to 2019 levels by 2023. We also model the impact of the policy supports available to firms. In the absence of government supports, the distress rate would have been seventy-two per cent higher during the pandemic. We find that supports have a persistent impact even after they expire. In 2024, the distressed rate without the supports would be twenty per cent higher than in the baseline scenario with supports.
Keywords: D22; L25; D04; H25; 330; Small and Medium-sized Enterprises; COVID-19; Policy Supports